Spotlight on pro-inflammatory chemokines: regulators of cellular communication in cognitive impairment - Wang, Chenxu; Wang, Jiayi; Zhu, Zhichao; Hu, Jialing; Lin, Yong (Frontiers in Immunology, 2024)
Cognitive impairment is a decline in people's ability to think, learn, and remember, and so forth. Cognitive impairment is a global health challenge that affects the quality of life of thousands of people. The condition covers a wide range from mild cognitive impairment to severe dementia, which includes Alzheimer's disease (AD) and Parkinson's disease (PD), among others. While the etiology of cognitive impairment is diverse, the role of chemokines is increasingly evident, especially in the presence of chronic inflammation and neuroinflammation. Although inflammatory chemokines have been linked to cognitive impairment, cognitive impairment is usually multifactorial. Researchers are exploring the role of chemokines and other inflammatory mediators in cognitive dysfunction and trying to develop therapeutic strategies to mitigate their effects. The pathogenesis of cognitive disorders is very complex, their underlying causative mechanisms have not been clarified, and their treatment is always one of the challenges in the field of medicine. Therefore, exploring its pathogenesis and treatment has important socioeconomic value.Chemokines are a growing family of structurally and functionally related small (8-10 kDa) proteins, and there is growing evidence that pro-inflammatory chemokines are associated with many neurobiological processes that may be relevant to neurological disorders beyond their classical chemotactic function and play a crucial role in the pathogenesis and progression of cognitive disorders. In this paper, we review the roles and regulatory mechanisms of pro-inflammatory chemokines (CCL2, CCL3, CCL4, CCL5, CCL11, CCL20, and CXCL8) in cognitive impairment. We also discuss the intrinsic relationship between the two, hoping to provide some valuable references for the treatment of cognitive impairment.